2021
DOI: 10.3390/cancers13061369
|View full text |Cite
|
Sign up to set email alerts
|

The MEK1/2 Pathway as a Therapeutic Target in High-Grade Serous Ovarian Carcinoma

Abstract: High-grade serous ovarian carcinoma (HGSOC) is the deadliest of gynecological cancers due to its high recurrence rate and acquired chemoresistance. RAS/MEK/ERK pathway activation is linked to cell proliferation and therapeutic resistance, but the role of MEK1/2-ERK1/2 pathway in HGSOC is poorly investigated. We evaluated MEK1/2 pathway activity in clinical HGSOC samples and ovarian cancer cell lines using immunohistochemistry, immunoblotting, and RT-qPCR. HGSOC cell lines were used to assess immediate and last… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 84 publications
3
34
0
Order By: Relevance
“…Expression of the MPAS gene signature is associated with MEK/ERK pathway activity across various tumors (29). Therefore, we used it to confirm MEK/ERK inhibition by trametinib in ovarian cancer (18). Most MPAS genes displayed prominent downregulation in response to trametinib, but two genes ( DUSP6 and CCND1 ) displayed inconsistent results, and EPHA4 expression levels were below reliable levels of detection.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Expression of the MPAS gene signature is associated with MEK/ERK pathway activity across various tumors (29). Therefore, we used it to confirm MEK/ERK inhibition by trametinib in ovarian cancer (18). Most MPAS genes displayed prominent downregulation in response to trametinib, but two genes ( DUSP6 and CCND1 ) displayed inconsistent results, and EPHA4 expression levels were below reliable levels of detection.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent analyses of accumulated genomic data revealed that HGSOC, while rarely harboring KRAS/BRAF mutations, still often displays amplifications and overexpression of MEK1/2 pathway elements (16). High MEK1/2 activity was experimentally confirmed in HGSOC cell lines and clinical samples and identified as a negative prognostic factor (17,18). MEK1/2 activation occurs in response to cisplatin and may render tumors resistant to platinum treatment (18)(19)(20).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Human OVCA line (SKOV3), purchased from ATCC (Manassas, VA, USA), was cultured in McCoy’s 5A medium (Sigma-Aldrich; St. Louis, MO, USA) containing 10% fetal bovine serum (FBS). Human Type I OVCA cell lines (TOV-21G and TOV-112D) [ 32 ], purchased from Bioresource Collection and Research Center (BCRC) (Hsinchu, Taiwan), were cultured in (MCDB105/Medium 199 1:1) medium (Gibco, Grand Island, NY, USA) containing 15% FBS. These cell cultures were supplemented with 100 U/mL penicillin and 100 μg/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%